Encapsulated Papillary Carcinoma: A Case Report and Review of the Literature - Athanasiou, Aikaterini; Khomsi, Fathi; de Joliniere, Bouquet; Feki, Anis (Frontiers in Surgery, 2022)
Papillary neoplasms are a distinct assemblage of breast lesions whose main characteristic is the presence of fibrovascular cores which are surrounded by epithelial cells (1,2). Papillary lesions are of heterogenous nature, with similar clinical behavior and histomorphologic characteristics. Τheir biological patterns, however, can be quite different (2). According to the World Health Organization (WHO) (2019), breast tumors have been recently classified into five subdivisions of papillary neoplasms. They are namely: intraductal papilloma, papillary ductal carcinoma in situ, encapsulated papillary carcinoma (EPC), solid‐papillary carcinoma and invasive papillary carcinoma (1,3). Despite the papillary architecture being easily recognized, histological variations are diagnostically challenging (2). The presence or absence of myoepithelial cells in the papillary cores can distinguish the malignant from the benign lesions respectively (1). EPC is a rare, histologically unique carcinoma type whose main characteristic is a thick fibrous capsule at the periphery and a prolific cell structure with fibrovascular stalk support (1). A characteristic feature is the absence of myoepithelial cells at the surrounding thick fibrous capsule (2, 4). Usually, EPC maintains a slowly developing tumor despite the absence of myoepithelial cells (1). An EPC case presents diagnostic difficulties since it bears close resemblance to malignant and benign papillary breast lesions (5). Upon a clinical and radiological evaluation, EPC commonly appears as a benign lump. In mammography, the tumor is frequently found in a retroareolar position as a well-defined mass (2). On the other hand, in an ultrasound, the tumor will appear as a cystic lesion characterized by solid components (2). The clinical picture of EPC is usually an asymptomatic benign mass which at times can be felt through auto-palpation or screening mammography (6). A bloody nipple discharge is regarded as a common symptom (6). We report a case of an EPC of a 81-year-old woman who presented with a mass in the left breast.